Fatigue behaviour of AA5052-H36 laser-welded overlap joints: Effect of stitch-weld orientation and gap bridging. (February 2023) - Idriss, Mohamad; Mirakhorli, Fatemeh; Desrochers, Alain; Maslouhi, Ahmed
Graphical abstract: Highlights: Defect-free laser-welded AA5052-H36 overlap joints were prepared using oscillation mode. Stitch weld orientation influences significantly the fatigue behaviour of overlap joints. Stitch weld orientation and fatigue load influence fracture patterns in overlap joints. Contrary to static loading, the gap reduces the fatigue performance of overlapped joints. Seven different mathematical models described satisfyingly the tested joints' fatigue curves. Abstract: This study investigates the fatigue behaviour of overlap laser-welded 1.6 mm thick AA5052-H36 sheets. The oscillation beam laser welding in continuous mode is adopted for preparing defect-free weld seams. Three different stitch-weld orientations (transversal, longitudinal, and diagonal with respect to the load direction, denoted in the present work A, B, and F, respectively) coupled with two different part-to-part gap values (in contact and out-of-range gaps, denoted G00 and G05, respectively) are considered. The vertical configuration showed the highest fatigue resistance and repeatability as well as the highest resistance to crack propagation and the most secure fracture pattern. Finally, the gap decreased the fatigue life in a range of 5–20 % depending on the applied load and the stitch-weld orientation.